Submerged aquatic plant (Vallisneria spiralis and Egeria densa) utilisation as a biogas cleaner and feedstock of co-digestion - Nagy, Gábor (International Journal of Engineering and Management Sciences, 2019)
Biogas was produced from sheep manure and two types of submerged aquatic plant (Vallisneria spiralis and Egeria densa). The gas cleaning was carried out by a water scrubber, where a significant part of CO2 and H2S can be separated from the gas. A part of water from the scrubber was circulated through an aquatic plant growth tank and the growth of used plants was examined. Addition of E. densa to sheep manure increased gas yield by 8% and the mixing of sheep manure and V. spiralis resulted in 21% increase in gas yield. With the used scrubber, 70-80 vol% methane content can be reached in the cleaned biogas, and the water from the scrubber (which contained dissolved CO2 and H2S) resulted in 56-87% increase in size as opposed to 12-44% increase in the control group.